ANALISIS STRATEGI PENGEMBANGAN USAHA PADA UKM BATIK SEMARANGAN DI KOTA SEMARANG - Alfi Amalia; Wahyu Hidayat; Agung Budiatmo (Universitas Diponegoro, 2012)
Micro, Small and Medium Enterprises (SMEs) have a strategic role in national economic development, because in addition to a role in economic growth and employment also play a role in the distribution of development outcomes. In the current economic crisis in our country some years ago, where many large-scale enterprises stagnated even stop their activities, Micro Small and Medium Enterprises (MSMEs) proved to be more resilient in the face of crisis. But there are also disadvantages of SMEs in accessing information that is directly related to the condition alleged internal factors are overshadowed by the SMEs SMEs that actually has a considerable market share of the international world, has not been known to consumers.Batik is Indonesia's cultural heritage adi noble. Almost every region in Indonesia has its own art and batik motif. No exception Semarang city has Semarangan batik hallmark. Problems faced by SMEs Batik batik Semarangan Semarangan the presence of less known by the public because of constraints on marketing and human resources are limited.The purpose of this study was to determine the company's strategy in developing alternative business Semarangan Batik using SWOT analysis. This research is a descriptive study with qualitative data support. Engineering data collection obtained through in-depth interviews with as well as real data from internal and external field.From the results obtained using SWOT analysis 13 strartegi alternatives: (1) Using modern technology to increase production (2) maintain the quality of the product (3) develop a business using financial aid from the government (4) provide training to the employee (5) Recruiting experts (6) Accounting for administration and finance (7) Working with wholesalers batik (8) Increasing the promotion through the internet especially when held SEMAGRES (9) Offering products keorganisasi or work group (10) Improving the quality of customer service (11) Increase design creative and interesting motifs (12) Increase of capital by lending to the government through the state-owned (13) Increase distribution channels.